Bridging the leadership gap: agency training and support shapes non-supervisors’ perceptions of their leaders - Madyson Popalis; Jonathon P. Leider; Avia Mason; Maya Najjar; Moriah Robins; Brian Castrucci (Frontiers in Public Health)
BackgroundStrong leadership is essential for government public health agencies to thrive, as it shapes critical factors like organizational culture, workforce engagement, and job satisfaction. Supervisors serve as key pathways to building and sustaining an effective public health workforce. To strengthen public health leadership, it is important to understand the training and support supervisors currently receive and how this influences the experiences of non-supervisory staff.MethodsThis analysis uses data from PH WINS 2024, a national survey of the state and local public health workforce. Respondents report on demographics, workforce characteristics, and workplace environment. Supervisors reported on agency-provided leadership training and support, while non-supervisors rated their satisfaction with supervisors. A multilevel logistic regression examined how agency and program level supervisor training and support related to non-supervisor satisfaction, adjusting for setting and respondent demographics.ResultsA total of 56,595 employees responded to the survey, with 28% identifying as supervisors. Many supervisors reported gaps in leadership development: 46% did receive initial leadership training, 41% did not receive initial organizational training, 27% do not receive ongoing leadership training, and 31% do not receive ongoing support as a supervisor. The multi-level logit model showed that supervisor satisfaction was more likely at agencies with higher levels of supervisor reported initial training (AOR 1.18, p = 0.003) and ongoing training (AOR 1.12, p = 0.036). Ongoing support showed the strongest association with supervisor satisfaction (AORs 1.14–1.38, all p < 0.005) in agencies where at least half of supervisors reported receiving support.ConclusionKey findings from this study indicate that non-supervisory staff report higher satisfaction with their supervisors in agencies where a greater proportion of supervisors received leadership training and have ongoing support. Developing leadership is a practical and powerful way to strengthen the government public health workforce. Prioritizing supervisor training and support as a foundational workforce strategy is key for improving workplace satisfaction. Strengthening public health leadership begins with creating consistent, well-resourced systems for preparing and supporting supervisors.